Potential environmental impacts of a plastic waste export ban in Germany - Strobel, Ronja; Hagedorn, Tabea; Lopes, Alice do Carmo Precci (Frontiers in Manufacturing Technology, 2023)
Up to 800,000 t/a of plastic waste generated in Germany is exported, of which more than a quarter is packaging. However, a sustainable waste management system aims at treating waste under consideration of environmental benefits generation and the reduction of negative environmental impacts. Thus, this brief research deals with the question to what extent negative environmental impacts could be avoided by an export ban. Further, this brief research serves as a preliminary basis for further discussions and studies in the field of the plastic export ban. Two scenarios were developed based on expert interviews to estimate alternative management for the otherwise exported plastic waste generated in Germany. A consequential life cycle assessment (LCA) was carried out to look into the possible Global Warming Potential changes of such scenarios compared to the current situation scenario. The LCA showed that an export ban in Germany offers the possibility of avoiding up to 80 CO2-equivalent per ton of exported packaging plastic. However, this would be only possible if most of the plastic packaging that is no longer exported is recycled and not burned for energy production in the case of Germany.